Study of river flow vulnerability to climate changes in urbosystems on the basis of sustainable development - Reshetchenko, A. (Scientific Progress & Innovations, 2022)
Climate change leads to a significant impact on water bodies. The relevance of the research covered in this article is primarily related to the implemented political orientation of Ukraine to achieve the goals of sustainable development, which was approved at the legislative level by the Presidential Decree. The fight against climate change and its consequences is defined as one of the primary goals and requires urgent measures. In Ukraine, the Concept of implementation of the state policy in the field of climate change for the period up to 2030 has been approved. The highlighted research results in this publication correspond to the 13 and 6 goals of sustainable development, such as "Combating climate change" and "Clean water and adequate sanitation". Data from systematic observations of water flow in the Lopan River from 1980 to 2019, obtained by the Kharkiv Regional Hydrometeorological Center at observation post No. 78371, Kozacha Lopan settlement, were used to study surface runoff changes. ERA5, the fifth generation ECMWF Global Climate Atmospheric Reanalysis, was used to analyze temperature changes and precipitation in the period from 1979 to 2021. Based on the results of processing the obtained observational data, it was determined that summer and winter temperatures have increased by almost 1.2–1.3 ºС over 30 years. According to the results of the calculations, it was found that the average volume of the Lopan river flow decreased from 86.5 in 1980 to 39.4 in 2020. According to the calculations of the modular coefficient for the period from 1980 to 2019, it is possible to trace the decrease in the water level of the Lopan River starting from 2007, which correlates with the decrease in the amount of precipitation in the Kharkiv region and the increase in the average annual temperature in the same period. The obtained results can be used for the implementation of local recommendations on the adaptation of water management to climate change, such as: shading the shoreline of the Lopan River and reconstruction of roads and optimization of traffic flow within the limits of influence on the Lopan River in the territory of Kharkiv Oblast.